2010
DOI: 10.1007/s00204-010-0588-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride-induced histopathology and synthesis of stress protein in liver and kidney of mice

Abstract: Selective low (15 mg sodium fluoride (NaF)/L) and relatively high (150 mg NaF/L) doses of in vivo fluoride (F) treatment to Swiss albino mice through drinking water elicited organ-specific toxicological response. All the F-exposed groups showed severe alterations in both liver and kidney architectures, but there was no significant change in the rate of water consumption and body weight. Vacuolar degeneration, micronecrotic foci in the hepatocytes, and hepatocellular hypertrophy were evident in the mice exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(69 citation statements)
references
References 19 publications
9
59
0
1
Order By: Relevance
“…*p < 0.05 significantly different from control, + p < 0.05 significantly different from 45 mg F − -treated rats (one-way ANOVA followed by Tukey's multiple comparison test) Earlier studies showed that elevated extracellular levels of Hsp70 serve as a prognostic marker for inflammatory cytokine-mediated immune response and the progression of heart failure in patients with acute AMI (Jenei et al 2013;Satoh et al 2006). Our results are in accordance with the report of Chattopadhyay et al (2011). Their findings showed the increased oxidative stress directly correlated with elevated Hsp70 expression in the mice kidney exposed to chronic F − intoxication.…”
Section: Resultssupporting
confidence: 91%
“…*p < 0.05 significantly different from control, + p < 0.05 significantly different from 45 mg F − -treated rats (one-way ANOVA followed by Tukey's multiple comparison test) Earlier studies showed that elevated extracellular levels of Hsp70 serve as a prognostic marker for inflammatory cytokine-mediated immune response and the progression of heart failure in patients with acute AMI (Jenei et al 2013;Satoh et al 2006). Our results are in accordance with the report of Chattopadhyay et al (2011). Their findings showed the increased oxidative stress directly correlated with elevated Hsp70 expression in the mice kidney exposed to chronic F − intoxication.…”
Section: Resultssupporting
confidence: 91%
“…Organ weight and Organosomatic index: Following humane sacrifice, the vital organs viz liver and kidney were excised, cleaned off the adhering tissue and weighed separately. The organo-somatic index (OSI) was calculated by using the following formula as per Chattopadhyay et al (2011). Organo -somatic Index (OSI) = Organ weight (g) / Live body weight (g) X 100 Sample preparation : For biochemical studies, 0.5 g of liver and one whole kidney was homogenized in 2 ml of phosphate buffer saline (PBS 0.1M, pH 7.4) and the homogenate was centrifuged at 3000 for r.p.m.…”
Section: Methodsmentioning
confidence: 99%
“…Chattopadhyay, S. Podder, S. Agarwal, and S. Bhattacharya, [11] have evidently specify the study of Fluoride (F)-induced hepatotoxicity and nephrotoxity in mice by analysing the histopathological changes in the liver, kidney and oxidative stress. To obtain an effective inducer, the Heat Shock Protein (HSP70) in kidney and the liver is negatively regulated in mouse.…”
Section: Literature Reviewmentioning
confidence: 99%